SCHOOL STAGE IMPLEMENTATION IN DEVELOPING EARLY CHILDREN'S PERFORMING ARTS CREATIVITY - Andi Ernawati; Cucum Sumiati; Buton Buton; Mia Sumiani Madi; Durrotul Muniroh Ahdaniyah (Universitas Panca Sakti Bekasi, 2023)
Performing arts creativity has an important role in the holistic development of early childhood. The implementation of the TV Sekolah stage in schools has been recognized as an effective approach to facilitating the development of early childhood performing arts creativity. The purpose of this research is to explore the implementation of the school stage in developing early childhood performing arts creativity. This study uses a qualitative descriptive method involving participatory observation, interviews, and document analysis. Research participants consisted of early childhood, educators, and parents who were involved in the School TV Sekolah stage program. The results of the study show that the implementation of the School TV Sekolah stage makes a positive contribution in developing early childhood performing arts creativity. Through the TV Sekolah school stage, children have the opportunity to express themselves, hone their performing arts skills, and broaden their knowledge of art and culture.